The State of Nature, the Original Position and the Problem of historical Memory - Castilla Urbano, Francisco (Anales del Seminario de Historia de la Filosofía, 2007)
The comparison between the concept state of nature, as it appears in the contractualist theories of XVII and XVIII centuries, and the original position of the the- ory of justice by John Rawls, reveals the assumptions, difficulties and limitations of the latter. In spite of its claims, the original position does not justify the search and existence of a well ordered society, and it is far away from reach the brightness and coherence with which their predecessors (Hobbes, Locke or Rousseau) argued on behalf of societies where safety, freedom or equality ruled. Besides, Rawls, on amounting justice to a material welfare which must arrive, does not know the important role that the historical memory plays when claiming the resolution of the injustices from the past